Five-Year Analysis of Measured and Calculated Dose Rates from Co60 Teletherapy Machine at Centre for Nuclear Medicine and Radiotherapy (CENAR) Quetta, Pakistan: A Comprehensive Assessment - Shafiq, Sunnia; Ahmad, Hafiz Khush Naseeb; Manzoor, Hina; Ur-Rehman, Awais; Naheed, Hameeda; Kanwal, Shagufta; Basit, Abdul; Ullah, Sadiq; Saeed, Hashir; Iftikhar, Shehla (Diponegoro University Semarang Indonesia, 2024)
This study assesses the dosimetry of a Cobalt-60 (Co60) teletherapy unit at the Centre for Nuclear Medicine and Radiotherapy (CENAR), Quetta, to ensure consistent radiation doses for cancer management. Dosimetry measurements were compared against expected outputs derived from the International Atomic Energy Agency's TRS-398 protocol and decay calculations. The current investigation demonstrates uniformity in average output (dose rate) between the actual dosimetry values and the anticipated output values obtained through the International Atomic Energy Agency's TRS-398 (2000) protocol and decay method respectively. The actual dosimetry values fall within a range of ±2% of the estimated values. The difference in measurements acquired through the two approaches falls within acceptable limits as per recommended protocols. Consequently, our study reveals a steady pattern in dose rate, ensuring improved patient dose distribution and minimizing the risk of over or under-dosage.